1991
DOI: 10.1080/02724936.1991.11747528
|View full text |Cite
|
Sign up to set email alerts
|

Low birthweight and acute childhood diarrhoea: evidence of their association in an urban settlement of Papua New Guinea

Abstract: Children under 5 years of age residing in an urban settlement of Papua New Guinea were monitored from May 1987 to July 1988 in an attempt to identify aetiological factors of childhood diarrhoea. Low birthweight was found to be strongly associated with diarrhoea (incidence density ratio (IDR) = 1.60, 95% confidence interval (CI) = 1.26-2.03). The low birthweight effect was noticeable to at least 3 years of age. Greater attention should be paid to reducing the incidence of low birthweight, because such a reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…Adjusting for a wide range of covariates, neither PI at birth or birthlength SDS was related to diarrhoeal incidence. This agreed with a study in rural Bangladesh (11), but disagreed with one in urban Papua New Guinea (3). Using birthweight and birthlength dichotomized according to ¡2 SDS as independent variables gave the same result of no association.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Adjusting for a wide range of covariates, neither PI at birth or birthlength SDS was related to diarrhoeal incidence. This agreed with a study in rural Bangladesh (11), but disagreed with one in urban Papua New Guinea (3). Using birthweight and birthlength dichotomized according to ¡2 SDS as independent variables gave the same result of no association.…”
Section: Discussionsupporting
confidence: 71%
“…However, the studies used different indicators for their outcome measures. Only one of them analysed diarrhoeal incidence (3), which better re ected the risk of acquiring diarrhoea (4). The others used hospitalization for diarrhoea (5)(6)(7), clinic attendance for diarrhoea (8) and prevalence (9) as outcomes.…”
mentioning
confidence: 99%
“…Birthweight also affects postnatal growth and development (Steer 2000). LBW infants have higher rates of intestinal and respiratory infections, higher rates of hospitalization, and higher mortality rates than appropriate weight infants (Victora et al 1990; Bartlett et al 1991;Bukenya et al 1991;Lira et al 1996;Ashworth 1998). Moreover, adults who were born with LBW are thought to be at increased risk of chronic diseases such as hypertension, non-insulin dependent diabetes mellitus, coronary heart disease and stroke (Barker 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Around 90% of all low birthweight infants are born in developing countries,1 mostly caused by intrauterine growth retardation (IUGR) rather than prematurity 45 Studies undertaken in Papua New Guinea have shown that acute diarrhoea6 and mortality from measles7 were significantly higher among low birthweight than among normal infants. Malarial infection during pregnancy is an important, and potentially preventable, environmental cause of low birthweight.…”
mentioning
confidence: 99%